Propagation of Lembah Palu Shallot Somatic Embryosas Effortsto Provide Good Quality Seed - Maemunah Maemunah; Ramal Yusuf; Hawalina Hawalina; Yusran Yusran (Universitas Tadulako, 2015)
Shallot (Allium wakegi Arakic.v. Lembah Palu) is a horticulture commodity prospective as a very good business opportunity, since becomes the major ingredient of fried shallot, the most unique souvenir of Palu. The productivity however, is generally low due to lack in availability of good seed and seed production technology. The purpose of this study is to develop seed production technology through multiplication of somatic embryos. This assessment is the second part of research stages regarding the development of shallotsomatic embryo technology in Central Sulawesi. The first stage of the research is setrilization and callus induction of Lembah Palu shallot. This second stage is maturation dan germination of somatic embryos.The experiment was arranged as factorial completely randomized design, comprising of two factors. The first factor was 2,4-D concentration; consisting of three levels i.e 0.00, 0.25 and 0.50 mg/L. The second factor is kinetin concentration with the same levels as in 2,4-D. Each treatment combination was replicated three times, thus there were 27 experimental units. The result showed that addition of kinetin in MS basal media strongly affected the percentage of mature embryos and the percentage of mature embyos producing shoots, with the highest rate was obtained from the media fortified with 0,50 mg/L kinetin (26,913% and 43,318% respectively). Addition of 2,4-D to the MS basal media tended to inhibit the rate of regenerating shoot from the embryos. There is no interaction between 2,4-D and kinetin concentrations in affecting maturation and germination of the somatic embryos.